Answer:
(3,-3)
y= -3
x= 3
Step-by-step explanation:
5x+2y=9
2x-3y=15
solve the equation
x=9/5-2/5y
2x-3y=15
substitute the value of x into an equation
2(9/5-2/5y)-3y=15
distribute
18/5-4/5y-3y=15
subtract -4/5 to -3
18/5-19/5y=15
subtract 18/5 from both sides
-19/5=57/5
divide both sides by -19/5
y= -3
substitute the value of y into an equation
x=9/5-2/5(-3)
distribute
x=9/5+6/5
add 9/5 to 6/5
x=3
--------
(3,-3)
--------
So first you need to open the brackets, so it would be x+2+4x-122=180. Then we can add the 4x and the other x to make 5x, and then by doing 2-122 we get -120. This gives us the equation 5x-120=180. We then isolate the variable by moving the -120 to the other side of the equation and becoming a positive, so it would look like 5x=180+120. Then, we have 5x=300. 300 divides by 5 is 60 making X=60. Hope this helps!
You would use 539 and square it on you cal. just once. Then once you do that the answer is not going to be a whole number it is going to have a decimal, so the answer would be 23.22.
Answer:
8y=-11x-48
You have to subtract 11x bc the standard for is y=mx+b